Т lymphocytes are key immune regulating cells - V. S. Sviridova; Ye. N. Коlogrivova; N. A. Pronina; L. V. Yeliseyeva; A. A. Chitalkina (Бюллетень сибирской медицины, 2007)
Phenotypical and functional heterogeneity of immune regulating subpopulations of T-lymphocytes having suppressor activity is discussed in the article. Natural regulators and inducible regulating cells are characterized in more details.